Creating identity in the Victorian fictional autobiography - Pennington, Heidi L. (University of Missouri Press, 2018)
"This is the first book-length study of the fictional autobiography, a subgenre that is at once widely recognizable and rarely examined as a literary form with its own history and dynamics of interpretation. Heidi L. Pennington shows that the narrative form and genre expectations associated with the fictional autobiography in the Victorian period engages readers in a sustained meditation on the fictional processes that construct selfhood both in and beyond the text. Through close readings of Jane Eyre, David Copperfield, and other well-known examples of the subgenre, Pennington shows how the Victorian fictional autobiography subtly but persistently illustrates that all identities are fictions. Despite the subgenre's radical implications regarding the nature of personal identity, fictional autobiographies were popular in their own time and continue to inspire devotion in readers. This study sheds new light on what makes this subgenre so compelling, up to and including in the present historical moment of precipitous social and technological change. As we continue to grapple with the existential question of what determines "who we really are," this book explores the risks and rewards of embracing conscious acts of fictional self-production in an unstable world"--